Translation as editorial mediation: Charles Estienne's experiments with the dissemination of knowledge. Issue 1 (February 2015) - Cazes, Hélène
<x xml:space="preserve">Abstract</x> Charles Estienne is the most versatile member of the French humanist dynasty of printers, the Estiennes, yet he has suffered from an unfavourable comparison with his father and brothers. This article accords him, at last, the respect he deserves. He authored a series of short compilations for young students between 1536 and 1540, printed in Paris and Lyon. These booklets, organized like beginners' dictionaries, propose a system of bridges between languages: Greek, Latin, and French. Presented as summaries, they can be read as attempts to structure and circulate knowledge according to a new 'printed' model, and they were reprinted and rearranged by Estienne in the 1550s, after he himself became a printer. His anatomical treatise, first published in Latin (1545) then in French (1546), also appears like a system of names and languages. As the translator of texts representing a wide variety of genres, Estienne plays on the different registers of the annotated edition, summary, compilation, and translation to effectuate the same trope: vulgarization, meaning accessibility for a great number of readers as well as translation into the vernacular. Similarly, the printing press addresses a great number of potential readers. The study enquires whether the technology of this first form of vulgarization calls for a second one, a 'vernacularization', whether printing also implies editing, and whether annotations and editions turn into translations. Taking Charles Estienne, the one‐man printer, editor, translator and annotator as a case study, I explore the meaning of 'vulgarization' in the typographical workshop.